Trade Policy and Market Power : Firm-Level Evidence - Asprilla, Alan; Berman, Nicolas; Cadot, Olivier; Jaud, Melise (World Bank, Washington, DC, 2019)
This paper identifies the effect of trade policy on market power through new data and a new identification strategy. It uses a large data set containing export values and quantities by product and destination for all exporting firms in 12 developing and emerging countries over several years, merged with destination-product-specific information on tariffs and non-tariff barriers. Market power is identified by observing how exporting firms price discriminate across markets in reaction to variations in bilateral exchange rates. Pricing-to-market is prevalent in all regions of the sample, even among small firms, although it is increasing in firm size, in accordance with theory. More importantly, the effect of non-tariff measures is not isomorphic to that of tariffs: the observed pricing-to-market behavior suggests that, although tariffs reduce the market power of foreign firms through classic rent-shifting effects, non-tariff measures alter market structure and reinforce the market power of non-exiting firms, domestic and foreign ones alike.